ENHANCING HUMAN CAPITAL’S PERFORMANCE THROUGH INNOVATIVE TRAINING MANAGEMENT: A CASE STUDY OF AZKIRA REG TRAINING INSTITUTION'S PLASMA MODEL - Badriah, Badriah; Saripah, Iip (Jurnal Empowerment, 2024)
This paper aims to describe human capital development through education and training programs that facilitatie immediate workplace application of knowledge and skills by their graduates upon completion of the training. In more particular, this paper portray the implementation process of the Plasma model in Azkira Reg's sewing training management. The study employed case study to elaborate the management innovation used in Azkira Reg sewing training and industry. The informal interview, observation, and documents were data collection technique. The results suggests that plasma model:1) was an innovative training management where training and industry interlock to provide graduates room to implement their knowledge and skills in a plasma as their workplace, 2) empower the training graduates upon their training completion by managing plasma, and 3) provided opportunities to continue leaning and grow.